A Race to the Top? A Case Study of Food Safety Standards and African Exports - Otsuki, Tsunehiro (World Bank, Washington, DC, 2014)
Growing concern over health risks associated with food products is at the forefront of trade policy debate. At the heart of this debate is the "precautionary principle," which holds that precautions should be taken against health, safety, and environmental risks even when science has not established direct cause-and-effect relationships--as with, for example, the EUropean ban on hormone-treated beef. The authors quantify the impact on food exports from African countries of new EUropean Union standards for aflatoxins, structurally related toxic compounds that contaminate certain foods and lead to the production of acute liver carcinogens in the human body. The authors estimate the impact of changes in differing levels of such protection based on the EU standards (and suggested by international standards) for 15 EUropean countries and 9 African countries between 1989 and 1998. The results suggest that implementation of the EU's new aflatoxin standards will significantly hurt African exports to EUrope of nuts, cereals, and dried fruits, which are highly sensitive to the aflatoxin standards. The EU standards would reduce health risks by only about 1.4 deaths per billion a year but would cut African exports by 64 percent, or $670 million, compared with their level under international standards.